PEMANFAATAN TEKNOLOGI AUGMENTED REALITY SEBAGAI MEDIA PEMBELAJARAN TATA SURYA BERBASIS ANDROID PADA SISWA TUNADAKSA - Syam, Supriadi; Mokram, Muh. Ilhamsyah; Ranteliling, Ratno (STMIK KHARISMA Makassar, 2024)
The solar system is one of the topics in natural science lessons taught in every school. However, school learning often relies solely on textbooks, which often do not explain the material in detail. This research aims to develop an Android-based application that utilizes augmented reality (AR) technology as a medium for introducing the solar system and to implement this AR technology. The method used in this research is the markerless method, which allows the development of AR without using special markers. This method is used to track objects in the real world and project them into the virtual world without requiring special markers. The research design uses UML (Unified Modeling Language), and the programming language used is C#. The result of this research is an Android-based solar system learning application. Based on the test results, the voice description is clearly audible, and the Star Tracking object can be detected well at a distance of 5 cm to 2 meters. Thus, it can be concluded that the markerless method can be implemented effectively.